Analysis of Management Factors Affecting Irrigated Wheat (Triticum aestivum L.) Yield Gap in Different Regions of Lorestan Province using the Comparative Performance Analysis (CPA) Method - Alinazar Nazari; Afshin Soltani; Ebrahim Zeinali; Alireza Nehbandani (بوم شناسی کشاورزی)
Introduction The global population is currently estimated to exceed 8 billion and is projected to reach approximately 10 billion by 2050. To meet the food demands of this growing population, global food production must increase by about 70%. However, several challenges hinder this goal, including changes in agricultural land use, environmental issues, declining soil fertility, water resource shortages, and the slowdown in yield growth of major cereals over recent decades. These challenges undermine the possibility of doubling global food production within the mentioned time frame. Therefore, strategies to increase yield potential and reduce the yield gap are critical components of achieving sustainable food security with minimal environmental harm. The yield gap is defined as the difference between potential yield and actual yield, which often exhibits significant variability. Inadequate agricultural management practices, such as improper planting dates, suboptimal seed rates, insufficient plowing, improper fertilization, nonuse of herbicides, and inefficient irrigation, are the main contributors to yield gaps in grain production.Materials and MethodsThis study was conducted to estimate the yield gap, identify the factors contributing to it, and determine the contribution of each factor in Lorestan province, covering counties with varying climatic conditions, including Khorramabad, Durood, Kouhdasht and Nourabad. For this purpose, management information from 240 irrigated wheat (Triticum aestivum L.) farms was collected during the 2022-2023 season. The yield gap was determined using the comparative performance analysis (PCA) method.Results and DiscussionThe results showed that the average yield in the surveyed farms in Khorramabad, Doroud, Kouhdasht, and Nourabad county was 5002, 5563, 4183 and 3333 kg.ha-1, respectively, With improved management, these yields could potentially increase to 10936, 11815, 6218 and 10936 kg.ha-1. Based on the findings: in Nourabad, the most influential factors in the yield gap were the amount of phosphorus fertilizer used (1004 kg.ha-1), number of plowing operations (320 kg.ha-1), amount of manure used (60 kg.ha-1) and harvest date (202 kg.ha-1). In Kouhdasht the yield gap was primarily due to the number of irrigations (1049 kg.ha-1), nonuse of pesticide (353 kg.ha-1), use of the Kouhdasht variety (463 kg.ha-1), and lodging (170 kg.ha-1). In Doroud, the use of Talaee variety (1951 kg.ha-1), number of top-dress fertilizer applications (1598 kg.ha-1), inclusion of corn in crop rotation (1083 kg ha-1), farmer's background (826 kg.ha-1), nonuse of herbicide (82 kg.ha-1), and farm area (469 kg.ha). In Khorramabad, sugar beet rotation (3246 kg.ha-1), number of irrigations (1269 kg.ha-1), planting date (841 kg.ha-1), pre planting irrigation (463 kg.ha-1), nonuse of herbicide (40 kg.ha-1), lodging (74 kg.ha-1) were identified as key contributors to the yield gap.ConclusionThe yield gap ranged from 1587 kg.ha-1 (32%) to 6252 kg.ha-1 (53%). The main factors contributing to the yield gap due to suboptimal management included the frequency of top-dress fertilizer applications, number of irrigations, crop cultivar selection, crop rotation practices, herbicide use, pest and weed control, as well as the amount and application methods of chemical fertilizers. The achievable yield gap across the studied climates and counties was estimated to range from 1,586 to 5,002 kg.ha⁻¹. Assuming an average achievable yield gap of 3000 kg.ha-1, and considering the area under irrigated wheat cultivation in the province, optimizing management practices could result in an annual wheat production increase of 148488 tons. This increase corresponds to approximately 80% of the province’s irrigated wheat production and 42% of its total wheat production. Since variables such as crop rotation, use of appropriate cultivars, number of irrigations, number of plowings, and planting date have a greater impact on the yield gap, optimizing these factors can significantly boost irrigated wheat yields. Considering the cost–income ratio, such optimizations would also be more profitable for farmers in the studied counties.